When "Nothing Happens": Navigating Between Denial and Negotiation in the Use of Digital Technologies in Education (Praxis Educativa, 2026)
This essay seeks to reflect, drawing on selected works and theoretical frameworks, on the contemporary challenges of integrating digital technologies into pedagogical practice in Argentina. Rather than attempting to encompass the entirety of existing scholarship on the subject, it engages with a set of contributions considered particularly relevant, which are subsequently analyzed and interwoven into a reflective process informed by the authors’ specific academic background and professional experience.
Keywords: Digital Technologies; Pedagogical Inclusion; Artificial Intelligence; Digital Education; Digital Citizenship